(untitled) (Italian Journal of Public Health, 2008)
Background: The increased risk of chronic diseases requires effective strategies to promote health, facilitating the adoption of proper life styles from childhood. In order to do that, the local health authority in Pavia has undertaken a pilot study with the aim of estimating the level of overweight and obese children in primary schools and of identifying the life styles that entail health risks. Methods: A cross-sectional study based on a sample of 460 children in their last year of primary school in the Province of Pavia was performed. Pupils were classified by Body Mass Index, and a face-to-face questionnaire about children’s use of time was administered. A multiple logistic regression analysis has been applied in order to identify risks or preventive health factors linked to physical activity and eating habits. Results: 12.6% of the children were obese and 26.3% overweight, with the percentage of obesity nearly double in those who do not practice organized sports activities at least once a week, in those who don’t have breakfast in the morning and in those who don’t spend their free time in movement games. From a multiple logistic regression it results that the risk of being obese is twice and three times higher for the children living respectively in medium and small towns than for the ones living in large towns. Conclusions: In the Province of Pavia the prevalence of overweight and obese 10-year-old children exceed the data reported in recent studies all over Italy. The life styles that entail obesity risks are significantly linked both to eating habits and to physical activity: living in middle- and small sized towns and not having breakfast before going to school emerge as risk factors, while practicing movement games in the free time after school appears to be a protecting factor.